Chimeric switch and inverted cytokine receptors in T cell therapy: reprogramming T cells to overcome immune suppression in the solid tumor microenvironment - Rane, Riley; Li, Fengqiao; Williams, Alexis; Jayadev, Avaneesh; Tran, Nhan L.; Winkles, Jeffrey A.; Kim, Gloria B. (Frontiers in Immunology, 2025)
Adoptive T cell therapy has transformed cancer treatment, with chimeric antigen receptor (CAR) T cell therapy demonstrating remarkable clinical success in hematological malignancies. By genetically engineering a patient’s own T cells to recognize and attack cancer cells, CAR T therapy has achieved durable remissions in several blood cancers. However, its efficacy in solid tumors remains limited, largely due to the immunosuppressive tumor microenvironment (TME), which impairs T cell infiltration, persistence, and function. To address these challenges, innovative strategies are being developed to reprogram T cell signaling within the hostile TME. One promising class involves chimeric non-antigen receptors (CNARs), which modulate T cell activity independently of direct antigen recognition. Among these, chimeric switch receptors (CSRs) convert inhibitory checkpoint signals into activating cues, while inverted cytokine receptors (ICRs) redirect suppressive cytokine signals to promote T cell activation. In this review, we provide a focused overview of the design principles, mechanistic functions, and therapeutic potentials of CSRs and ICRs as adjuncts to CAR T therapy in solid tumors. We also discuss key considerations regarding safety, specificity, and clinical translation to inform future advancements in engineered receptor strategies for cancer immunotherapy.